The Effect of Information Dissemination in Social Media on Consumer Stockpiling Behavior during Covid-19 Pandemic - Haudialwan, Mohammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
During the Covid-19 pandemic, stockpiling became a common phenomenon, when people flocked to markets or supermarkets to buy various needs ranging from food to the need for health equipment. Therefore, it is important to explore the stockpiling behavior that occurs in order to get a clearer picture of this phenomenon. This study aims to find out how the dissemination of information on social media containing stimuli affects consumer perceptions of perceived benefits of stockpiling until the consumer decides to stockpile in the end. This study is a survey study collected through a questionnaire employed online through social media (Whatsapp and Instagram). The data is analyzed quantitatively utilizing the PLM-SEM app. The results of this study show that received risk, perceived severity, and perceived scarcity do not have a significant effect on the perceived benefits of stockpiling and stockpiling, but social norms have a significant effect on the perceived benefits of stockpiling. The result can become a reference for determining policies in the face of the panic buying phenomenon which leads to stockpiling. Therefore, the media must realize that the content they publish must be free from exaggerated news so that they can provide real information to the public.